Historical-structural approach to the definition of the right to freedom of expression - Е. В. Тітко (Теорія і практика правознавства, 2016)
The article is disclosed to the problem of freedom expression. Special role taken to the analysis definition freedom of expression in special conditions of the different spheres. There are main complex approach to structural definition and to the right freedom of expression interpreting with features of historically-time term and taking into consideration a role of the man as persons for possibility existence democratic socially-state system